Difference in hydration structures between F-actin and myosin subfragment-1 detected by small-angle X-ray and neutron scattering - Matsuo, Tatsuhito (Biophysics (Nagoya-shi), 2013)
Hydration structures around F-actin and myosin subfragment-1 (S1), which play central roles as counterparts in muscle contraction, were investigated by small-angle X-ray scattering (SAXS) and small-angle neutron scattering (SANS). The radius of gyration of chymotryptic S1 was evaluated to be 41.3±1.1 Å for SAXS, 40.1±3.0 Å for SANS in H(2)O, and 37.8±0.8 Å for SANS in D(2)O, respectively. The values of the cross-sectional radius of gyration of F-actin were 25.4±0.03 Å for SAXS, 23.4±2.4 Å for SANS in H(2)O, and 22.6 ± 0.6 Å for SANS in D(2)O, respectively. These differences arise from different contributions of the hydration shell to the scattering curves. Analysis by model calculations showed that the hydration shell of S1 has the average density 10–15% higher than bulk water, being the typical hydration shell. On the other hand, the hydration shell of F-actin has the average density more than 19% higher than bulk water, indicating that F-actin has a denser, unusual hydration structure. The results indicate a difference in the hydration structures around F-actin and S1. The unusual hydration structure around F-actin may have the structural property of so-called “hyper-mobile water” around F-actin.